2005
DOI: 10.1074/jbc.m509438200
|View full text |Cite
|
Sign up to set email alerts
|

FlhB Regulates Ordered Export of Flagellar Components via Autocleavage Mechanism

Abstract: The bacterial flagellum is a predominantly cell-external supermacromolecular construction whose structural components are exported by a flagellum-specific export apparatus. One of the export apparatus proteins, FlhB, regulates the substrate specificity of the entire apparatus; i.e. it has a role in the ordered export of the two main groups of flagellar structural proteins such that the cell-proximal components (rod-/hook-type proteins) are exported before the cell-distal components (filament-type proteins). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
138
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(151 citation statements)
references
References 42 publications
5
138
0
5
Order By: Relevance
“…In addition to the structural components of the inner and outer rings of the NC (PrgH, PrgK, and InvG) (6) and the needle and inner rod proteins (PrgI and PrgJ) (17,18), we detected the export apparatus components InvA (19), SpaP, and SpaS (20) (Table S1). To validate the interaction of the export apparatus components with the NC base, we immunoprecipitated the complex from a strain carrying a carboxy terminal FLAG-epitope tagged allele of SpaS (SpaS N258A ), which carries a mutation in its catalytic, autoprocessing site, thus preventing the cleavage of its carboxyl terminus (21,22). Proteins affinity purified with an anti-FLAG antibody were separated by BN-PAGE, and the band corresponding to the NC was analyzed by LC-MS/MS.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the structural components of the inner and outer rings of the NC (PrgH, PrgK, and InvG) (6) and the needle and inner rod proteins (PrgI and PrgJ) (17,18), we detected the export apparatus components InvA (19), SpaP, and SpaS (20) (Table S1). To validate the interaction of the export apparatus components with the NC base, we immunoprecipitated the complex from a strain carrying a carboxy terminal FLAG-epitope tagged allele of SpaS (SpaS N258A ), which carries a mutation in its catalytic, autoprocessing site, thus preventing the cleavage of its carboxyl terminus (21,22). Proteins affinity purified with an anti-FLAG antibody were separated by BN-PAGE, and the band corresponding to the NC was analyzed by LC-MS/MS.…”
Section: Resultsmentioning
confidence: 99%
“…15 Ferris et al proposed a cleavage mechanism for the flagellar paralog of YscU, FlhB, in which the protein undergoes auto-cleavage of the peptide bond between asparagine and proline at the conserved NPTH site, and Zarivach et al have recently provided structural evidence to support such an intein-like, auto-cleavage mechanism involving asparagine cyclization by determining the crystal structure of the E. coli YscU ortholog EscU in the cleaved form along with several structures of uncleaved mutants. 15,18 The autocleavage mechanism requires a specific conformation of the NPTH loop in which the NPTH sequence adopts a type II b-turn, giving rise to a strained conformation that is required for efficient catalysis to occur. The cleavage reaction is initiated by the lone pair of electrons associated with the side chain Nd atom of N263 attacking the partially positively charged P264 carbonyl carbon atom to create a cyclized tetrahedral intermediate.…”
Section: Structure Determinationmentioning
confidence: 99%
“…has been shown earlier that YscU auto-proteolysis followed by YscU CC dissociation constitute critical steps for regulation of the substrate specificity switch (14,29,30). In addition, we recently showed that YscU CC is secreted by the T3SS when bacteria are grown in conditions allowing Yop secretion (26).…”
Section: Deletion Of the C Terminus Of Yscu Affects Yscf Secretion-itmentioning
confidence: 87%
“…Several studies have demonstrated the involvement of the YscU/FlhB family of protein in the substrate specificity switch (11,13,14,34). YscU is anchored in the inner membrane via four transmembrane segments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation